Holocaust education 25 years on: challenges, issues, opportunities. Issue 3 (3rd July 2017) - Pearce, Andy; Chapman, Arthur
ABSTRACT: This essay provides an introductory overview to the articles contained within this special issue. It suggests that the recent passage of 25 years since the Holocaust first appeared as a statutory subject in the English National Curriculum represents a key moment to "mark time": that is, to make the first moves in constructing an anthropology of Holocaust education in the postmodern epoch. It is argued that the need for this is pressing, not least because landmark research by the UCL Centre for Holocaust Education has highlighted serious issues in relation to students' knowledge and understanding of the Holocaust. This national research has international significance, and is used in this special issue as the starting point for reflections from both educators and historians in England and beyond.